In Situ Inhibitor Synthesis and Screening by Fluorescence Polarization: An Efficient Approach for Accelerating Drug Discovery. Issue 45 (11th October 2022) - Li, Zhihong; Wu, Yue; Zhen, Shuai; Su, Kaijun; Zhang, Linjian; Yang, Fulai; McDonough, Michael A.; Schofield, Christopher J.; Zhang, Xiaojin
Abstract: Target‐directed dynamic combinatorial chemistry has emerged as a useful tool for hit identification, but has not been widely used, in part due to challenges associated with analyses involving complex mixtures. We describe an operationally simple alternative: in situ inhibitor synthesis and screening (ISISS), which links high‐throughput bioorthogonal synthesis with screening for target binding by fluorescence. We exemplify the ISISS method by showing how coupling screening for target binding by fluorescence polarization with the reaction of acyl‐hydrazides and aldehydes led to the efficient discovery of a potent and novel acylhydrazone‐based inhibitor of human prolyl hydroxylase 2 (PHD2), a target for anemia treatment, with equivalent in vivo potency to an approved medicine. Abstract : In situ inhibitor synthesis and screening (ISISS) links high‐throughput bioorthogonal synthesis with screening tor target binding by fluorescence, as exemplified by the efficient identification of in vivo orally active inhibitors of PHD2, a target for anemia treatment.